2018
DOI: 10.1097/brs.0000000000002735
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cited Works in Spinal Disorders

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 110 publications
0
26
0
Order By: Relevance
“…A recent study published in 2018 by Badhiwala et al found that of the top 100 most cited articles published in journals dedicated to the field of spine, an astounding 84 were published in Spine. 22 A 2013 article also found Spine to be the most cited orthopedic journal, which is a testament to the pioneering nature of this journal since its inception 43 years ago. 23 This present study highlights landmark publications that have led the understanding of spinal pathology and development of current management modalities in spine care.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study published in 2018 by Badhiwala et al found that of the top 100 most cited articles published in journals dedicated to the field of spine, an astounding 84 were published in Spine. 22 A 2013 article also found Spine to be the most cited orthopedic journal, which is a testament to the pioneering nature of this journal since its inception 43 years ago. 23 This present study highlights landmark publications that have led the understanding of spinal pathology and development of current management modalities in spine care.…”
Section: Discussionmentioning
confidence: 95%
“…Since it was first published in 1976, Spine has been on the forefront of publishing impactful literature on matters involving the spine. A recent study published in 2018 by Badhiwala et al found that of the top 100 most cited articles published in journals dedicated to the field of spine, an astounding 84 were published in Spine 22 . A 2013 article also found Spine to be the most cited orthopedic journal, which is a testament to the pioneering nature of this journal since its inception 43 years ago 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The Web of Science database was used for this citation analysis. [10–27] The keywords included “whiplash,” “whiplash injury,” whiplash injuries,” “whiplash-associated disorder,” and “whiplash-associated disorders.” [4,8] The literature search was carried out on January 6th, 2022. No limitation was used in the publication time or article type.…”
Section: Methodsmentioning
confidence: 99%
“…Although the number of citations is not the only surrogate for determining the quality of scholarly works, it provides valuable data to determine classics that have shaped medical practice, fostered new research ideas, and predicted emerging trends and hotspots. [5][6][7] Several citation analyses have been conducted regarding various medical specialties and subspecialties, including diabetes [8][9][10] and podiatric medicine. [11][12][13] While studies on the diabetic foot comprise over a quarter of the top-cited publications in the field of foot and ankle surgery, 12 only a single bibliometric review has specifically addressed DFU to date.…”
Section: Introductionmentioning
confidence: 99%